INVESTIGATING THE ROLE OF THE TAD PILUS IN THE BACTERIAL BIOFILM LIFECYCLE - Karnani, Sahil (My University, 2024)
Biofilms, which are microbial communities that adhere to surfaces, pose a significant challenge to human health as they often lead to the emergence of multi-drug tolerant bacteria. The Type IV pilus (T4P) is a family of bacterial appendages that are critical to the formation of biofilms. There are three distinct T4P assembly systems: T4a, T4b, and Tad (tight adherence pilus). Prior experiments have shown that the Tad pilus may influence biofilm formation, however the mechanisms that drive this are not well understood. This thesis investigates the role of the Tad pilus in biofilm formation in P. aeruginosa. Our results demonstrate that increased expression of the transcriptional regulator pprB upregulates biofilm formation in a Tad pilus-dependent manner. Auto-aggregation assays and phase-contrast microscopy reveal that the Tad pilus facilitates interbacterial adhesion, a critical step in biofilm formation. Recent advancements have identified important structural components of the Tad pilus; however, the role of inner membrane components of this system has remained unclear. We identified that the uncharacterized protein RcpC is required to enhance Tad pilus-dependent biofilm formation. Structural analysis of RcpC revealed it forms a 12-membered ring with a 4.4 nm pore, which fits the 4.3 nm wide Tad pilus polymer that is extruded from the cell. We also show that the C-terminus of RcpC interacts with the Ig-like fold of the outer membrane pilus pore protein RcpA to form a stable complex that is required for Tad pilus assembly and function. Overall, these findings enhance our understanding of Tad pilus assembly and its role in biofilm formation, highlighting the importance of the RcpC-RcpA interaction in facilitating the polymerization and extrusion of the mature Tad pilus. This study also provides us with critical insights into the molecular mechanisms of the Tad pilus and its contribution to bacterial adhesion and the biofilm lifecycle.
Keywords: microbiology; bacteriology; biochemistry